A Phenomenological Study of Contemporary Minangkabau Preachers on Instagram - Riki Rikarno; Siti Fadilla; Aba Mele Maloum Oumar; Egil Novi Yendri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The rise of algorithmic platforms such as Instagram has transformed the practice of da’wah from traditional face-to-face religious gatherings into a digital public sphere governed by algorithmic logic. This shift has created tensions between conveying the substantive teachings of Islam and meeting the demands of digital visibility driven by user engagement. This study seeks to explore the lived experiences of contemporary Minangkabau da’i (Islamic preachers) and their audiences as they interpret, experience, and negotiate da’wah practices on Instagram. Employing an Interpretative Phenomenological Analysis (IPA) approach and using Heidi A. Campbell’s framework of religious digital creatives as an analytical lens, data were gathered through in-depth interviews with three Minangkabau da’i actively using Instagram, alongside focus group discussions with their audiences, followed by interpretative thematic analysis. The findings reveal three key insights. First, religious authority has evolved into a hybrid form that combines scholarly legitimacy with digital performativity. Second, religious meaning is co-constructed through a triadic relationship involving the da’i, their audiences, and the algorithms. Third, algorithmic pressures encourage the commodification of da’wah while simultaneously generating existential consequences, including anxiety, guilt, and a crisis of meaning (apologetic failure). This study contributes to the advancement of digital da’wah scholarship by conceptualising algorithms as active agents shaping religious experience and by emphasising the importance of algorithmic literacy and platform transparency in safeguarding the quality and integrity of religious communication.